Electrochemical and spectroelectrochemical properties of novel lutetium(III) mono- and bis-phthalocyanines - Arici, Mursel; Bozoglu, Ceyda; Erdogmus, Ali; Ugur, Ahmet Lutfi; Koca, Atif (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Peripherally and non-peripherally substituted-mono and sandwich lutetium(III) phthalocyanines bearing 3,4-(dimethoxyphenylthio) substituents have been synthesized and characterized by elemental analysis, FT-IR, UV-vis spectroscopy and mass spectroscopy. Voltammetric, in-situ spectroelectrochemical, and in-situ electrocolorimetric characterization of the newly synthesized phthalocyanines were performed in solution. Changing the number and the position the substituents altered the reversibility of the electron transfer processes and affected the easy of electron transfer reactions. While the mono phthalocyanines had an oxidation reduction peak separation (Delta E-1/2) higher that 1.50V, this value decreased up to 0.36V due to the pi-pi interaction of phthalocyanine rings around the lutetium core. Solvent of the electrolytic system also affected the redox behaviors of the complexes considerably. In-situ electrocolorimetric method was applied to investigate the color of the electrogenerated anionic and cationic forms of the complexes for their possible electrochromic applications. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Electrochemistry, Lutetium; Bis-phthalocyanines; Spectroelectrochemistry; Electrocolorimetry; Electrochromism; LANGMUIR-BLODGETT-FILMS; GLASSY-CARBON ELECTRODE; DOUBLE-DECKER; IN-SITU; ELECTROCHROMIC BEHAVIOR; DIPHTHALOCYANINE FILMS; SPECTRAL PROPERTIES; COMPLEXES; METALLOPHTHALOCYANINES; COBALT(II); Electrochemistry